Integrative Nutrigenomic Systems Biology Analysis of Traditional Chinese Medicine Interventions in Parkinson’s Disease: Nutrient-Gene-Disease Network Perspectives - Elham Amjad; Babak Sokouti (OBM Genetics, 2026)
The pathology of PD is characterized by progressive degeneration of dopaminergic neurons, although the full regulatory network involved in this process is not yet fully established. The present research employed a multi-omic systems biology design, integrating transcriptomic, functional, epigenetic, and microRNA analyses to develop a mechanistic model of neurodegeneration in the substantia nigra. We have determined six differentially expressed genes, such as tyrosine hydroxylase (TH), solute carrier family 18 member 2 (SLC18A2/VMAT2), and engrailed 1 (EN1), that are of critical interest in the disruption of the dopaminergic synapse and the inability to load vesicular neurotransmitters (fold enrichment: 2164.22). Notably, we have identified a candidate dual regulatory axis underlying the silencing of these neuroprotective genes. In this mechanism, repressive histone marks (H3K27me3 and H3K9me3) are concurrent, and post-transcriptional repression via specific microRNAs, in particular, hsa-miR-431-3p (EN1) and mmu-miR-362-5p (SLC18A2), is involved. The combined model thus finds a mutual dysregulation of epigenetics and microRNA as the main cause of gene silencing. Besides, the Traditional Chinese Medicine (TCM) components were analyzed to identify compounds that can interact with the core targets (TH and SLC18A2), thereby providing translational potential. The results identify candidate TCM compounds predicted to interact with core targets (TH and SLC18A2), providing hypothesis-generating leads for multi-target interventions that may modulate the repressive epigenetic landscape, suppress regulatory microRNAs, and engage dopaminergic pathways. Predicted interactions require experimental validation to distinguish beneficial modulation from potential inhibition. This would seek to reverse severe neuronal activity and halt the advancement of Parkinson's disease. These findings illustrate a neuro-nutrigenomic application in which dietary-derived and herbal compounds may modulate gene expression and epigenetic marks in Parkinson’s disease.